PENGARUH PENGGUNAAN VISCOCRETE-10 DAN SERAT BAN BEKAS TERHADAP NILAI SLUMP DAN KUAT TEKAN BETON SERAT - Agus Maryoto; Gandjar Pamudji (Dinamika Rekayasa, 2007)
Decomposed of tire waste is too difficult. The tire waste has good resistance against sea water and acids attack in long time and cause not significantly damages. The tire waste as fiber has moderate tensile strength, so that can used on concrete structure very well. This research is conducted to find the influence of viscocrete-10 towards slump value and compressive strength of fiber concrete. The viscocrete-10 dosage is 1 liter per cubic meter of concrete. The waste tire fiber sizes are 1 mm x 1 mm cross section and 1 mm, 5 mm, 10 mm, 25 mm, 50 mm and 75 mm length. Concentration of the waste tire fiber is 2.5% by volume. The research results show that the using of viscocrete-10 can increase workability of fresh fiber concrete, waste tire fiber can increase flexural strength of concrete except fiber 75 mm length decrease slump value amount 4 cm. Normally fiber addition cause decrease workability of fresh concrete. Meanwhile, fiber 10 mm length cause concrete compressive strength decrease 19.77% and fiber 75 mm length decrease compressive strength of concrete up to 28.88% than normal concrete.